Injuries in medium to long-distance triathlon: A retrospective analysis of medical conditions treated in three editions of the ironman competition - Feletti, F.; Saini, G.; Naldi, S.; Casadio, C.; Mellini, L.; Feliciani, G.; Zamprogno, E. (Journal of Sports Science & Medicine, 2022)
Triathlon`s popularity is rapidly increasing, and epidemiological data relating to its related medical conditions is crucial to the development of proper medical plans and safety guidelines for it. This study examined the data from the medical reports collected during three consecutive editions of Ironman Italy, from 2017 to 2019. Out of 10,653 race-starters, 3.3% required medical attention sustaining 472 medical conditions. A significantly higher injury risk was found for females versus males (?2 = 9.78, p = 0.02) and in long-distance (IR: 4.09/1,000hours) rather than in Olympic/middle distance races (IR: 1.75/1,000hours). Most (68.4%) conditions (including muscular exhaustion, hypothermia, and dehydration) were systemic, whilst only 10.2% were acute traumatic injuries. Of a total of 357 triathletes requiring medical assistance, 8.1% were a candidate for hospitalisation. The equipment and personnel that are required for the medical assistance in future triathlon events were estimated based on Maurer`s algorithm, and ten practical recommendations for triathlon medical support were formulated.